Yield Bioethanol From Pineapple Skin Waste With Yeast Mass And Fermentation Time - Siti Khuzaimah; Norma E (Program Studi Teknik Kimia, Universitas Pamulang, 2021)
Pineapple is a fruit that is commonly used by Indonesian people as a food ingredient. With the large production of pineapple, the amount of waste generated is also large, especially pineapple peel waste. The sugar content is quite high from the results of the study, it is known that the glucose content is 15.6% so that it can be utilized to produce bioethanol by further fermentation process by distillation. The purpose of this study was to determine the highest amount of ethanol in the variation of fermentation time and yeast weight. The process of making bioethanol in the early stages through the extraction process produces pineapple skin juice, then the fermentation stage at pH 4.5 using yeast and urea for optimal yeast growth and proliferation. To separate ethanol by the distillation process. In this study, variations in fermentation time were 2,4,6,8,10 and 12 days and yeast weight variations were 2,4,6,8, and 12 grams/200 mL. The results obtained for the optimal fermentation time produced the highest ethanol yield at 6 days of fermentation of 32.45% while the yeast used to produce the optimal ethanol yield was 4 grams and the ethanol yield was 30.78%.